2016
DOI: 10.1038/srep39586
|View full text |Cite
|
Sign up to set email alerts
|

Axonal branching in lateral olfactory tract is promoted by Nogo signaling

Abstract: Mitral cells are major projection neurons of the olfactory bulb (OB) that form an axonal bundle known as the lateral olfactory tract (LOT). After axonal bundle formation, collateral branches sprout from primary axons of the LOT. Recently, we identified LOT usher substance (LOTUS) as an endogenous Nogo receptor-1 (NgR1) antagonist and demonstrated that LOTUS contributes to the formation of the LOT axonal bundle. Immunoblots revealed that the expression level of Nogo-A in the OB developmentally increased during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…To explore the transport path from the olfactory region to the brain and to study kinetics of distribution and elimination, study 3 was designed with two different murine IgG antibodies and a scFv. The IgG1 antibody 11C7 binds to Nogo-A, which is predominantly expressed within the CNS but some reports have detected it in OSN [31,32]. The 11C7 was used as it is a promising antibody for multiple sclerosis or similar neurodegenerative diseases as it was shown that 11C7 therapy induces neuronal outgrowth in studies performed by Schwab and coworkers [33][34][35][36][37].…”
Section: Antibody Cns Distribution After Region-specific Intranasal A...mentioning
confidence: 99%
“…To explore the transport path from the olfactory region to the brain and to study kinetics of distribution and elimination, study 3 was designed with two different murine IgG antibodies and a scFv. The IgG1 antibody 11C7 binds to Nogo-A, which is predominantly expressed within the CNS but some reports have detected it in OSN [31,32]. The 11C7 was used as it is a promising antibody for multiple sclerosis or similar neurodegenerative diseases as it was shown that 11C7 therapy induces neuronal outgrowth in studies performed by Schwab and coworkers [33][34][35][36][37].…”
Section: Antibody Cns Distribution After Region-specific Intranasal A...mentioning
confidence: 99%
“…It is important to note that the developmental time point when myelin becomes abundant is much later than the appearance of nascent axon growth cones; thus, it is unlikely that MAIs play a major role in shaping neuronal networks (McKerracher and Rosen, 2015). Nonetheless, there are numerous studies examining the impact of several inhibitory molecules, especially the semaphorins, on various neurodevelopmental events (Iketani et al, 2016;Wang L. et al, 2017), but these are outside the scope of this review.…”
Section: Oligodendrocyte-axonal Growth Cone Interactionsmentioning
confidence: 99%
“…High sensitivity to the inhibitory effects of Nogo-A was detected in RGC axons (37,38). Nogo-A is highly upregulated in RGC axons, when the axons maturate and elongate in the presumptive optic nerve towards the brain (39), that is associated with collateral branches development (16,40). We observed that NOGO-A was strongly elevated in hRPE cells in HAF culture.…”
Section: Discussionmentioning
confidence: 63%
“…As HAF has shown neural transdifferentiation effect on hRPE cells (30,31), the elevated expression of NOGO-A in the treated cells can be explained as the regulatory role of Nogo-A and its receptors in neurite branching and extension that occur in the development of nervous system. Nogo receptor (NgR) has inhibitory effects on neuronal axon growth (21,40). NgR can interact with integrins, to decrease integrin activity and cell-substrate adhesion and a transactivation of the epidermal growth factor (EGF) receptor involving in cell migration and growth (41,42).…”
Section: Discussionmentioning
confidence: 99%